Membangun Kesiapan Professional Mahasiswa Akuntansi Melalui Praktikum Auditing Yang Terstruktur: (Studi Kasus Pada Mahasiswa D3 Akuntansi Politeknik Negeri Ambon) - Andriany, Dynne; Intan Ramadhani Bin Taher (Journal of Applied Accounting, 2025)
This study aims to see to what extent the auditing practicum course can build professional readiness of D3 accounting students at Ambon State Polytechnic. The focus of this study is on the structure and implementation of practicums for developing skills and professional readiness, objectivity of assessment and material development. The method used is a descriptive qualitative method through structured interviews. The results of this study are that auditing practicums have a large role in students in the process of building professional readiness, where the structure and implementation of practicums can help students understand the audit process in real terms. Students feel that by taking audit practicum courses they can develop their self-confidence and skills and professional readiness in facing the world of work later. However, some students felt that there was not enough time for guidance and development of the practicum which still used the practicum book. On average, students gave suggestions that the accounting practicum could use certain applications so that in practice, students could be more applicable and really feel the atmosphere of the working world as a reliable auditor. Keywords: professional readiness, Auditing practicum